Comparative study on the cardioprotective effects against ischemia/reperfusion injury of the selective SGLT2 inhibitors, empagliflozin, dapagliflozin and ertugliflozin in non-diabetic mice. (14th October 2021) - Mylonas, N; Nikolaou, P.-E; Efentakis, P; Dimitriadis, G; Iliodromitis, E K; Andreadou, I
Abstract: Background/Introduction: The sodium glucose co-transporter 2 selective inhibitors (SGLT2i) empagliflozin (EMPA), dapagliflozin (DAPA) and ertugliflozin (ERTU) are established drugs against type 2 diabetes mellitus (T2DM). However, the clinical outcomes among them differ; EMPA and DAPA treatment significantly reduced the frequency of cardiovascular events, while ERTU did not reach this endpoint. Thus, the comparative cardioprotective properties and further mechanistic insights for each SGLT2i should be elucidated. Purpose: We have previously proved that chronic EMPA administration reduces infarct size (IS), independently of the presence of T2DM in vivo. We aimed to 1) investigate the comparative cardioprotective effect of EMPA, DAPA and ERTU in terms of IS reduction upon short term administration and 2) reveal the mechanisms of cardioprotection in non-diabetic mice. Methods: Adult C57BL/6 mice were randomized into four groups and orally received EMPA (10mg/kg/day), DAPA (9.0mg/kg/day), ERTU (9.7mg/kg/day) or vehicle (5% DMSO in water for injection) for 7 days. The doses of DAPA and ERTU were stoichiometrically equivalent to EMPA's dose that we have previously used as clinically relevant. On the 8th day, mice were subjected to 30' ischemia (I), following by 2h reperfusion (R) and IS was measured. Body weight and fasting blood glucose levels were determined at baseline and at the end of the treatment. Then, we sought to unveil the mechanistic differences among those drugs which are responsible for the observed cardioprotection. Additional mice were randomized into the four groups and were treated for 7 days, as described above. On the 8th day, mice were subjected to 30'I/10'R and the ischemic myocardium was collected. We focused on the cardioprotective signaling of SAFE and RISK pathways and we evaluated the phosphorylation and expression of STAT3, PI3K, Akt and eNOS. Also, we examined the gene expression levels of IL-6 and TGF-β as possible mediators of the SAFE pathway. Results: Short term oral administration of EMPA and DAPA reduced myocardial IS (19.6%±2.6 EMPA, 18.0%±3.3 DAPA vs. 35.3%±1.7 Control, p<0.01). On the contrary, administration of ERTU did not reduce IS (30.3%±3.1 ERTU, p=NS). Body weight and glucose levels remained unchanged. Phosphorylation of STAT3(Y705) was increased at the 10th min of R in EMPA and DAPA groups, while was not altered by ERTU. Phosphorylation and expression of PI3K, Akt and eNOS did not differ among groups, indicating that the cardioprotective mechanism is independent of RISK pathway. Real time PCR analysis revealed that il-6 mRNA levels were not affected by the treatments. Notably, we observed increased mRNA levels of tgf-β in both EMPA and DAPA groups, which indicates that cardioprotection is mediated through STAT3/TGF-β crosstalk. Conclusion(s): Short-term EMPA and DAPA, but not ERTU treatment for 7 days reduces IS in healthy, non-diabetic mice through STAT3/TGF-β mediated pathways. Funding Acknowledgement: Type of funding sources: None.